One-stage combined ENT and dental surgical treatment of odontogenic sinusitis: a prospective study - Kocum, Petr; Šedý, Jiří; Traboulsi, Joseph; Jirák, Petr (European archives of oto-rhino-laryngology, 2024)
PURPOSE: The study analyses outcomes of the surgical treatment of odontogenic sinusitis that concurrently address sinusitis and its dental source. METHODS: A total of 364 adult patients were included, representing 13% of all patients we have operated on for any rhinosinusitis over the past 18 years. The diagnosis was based on both ENT and dental examinations including CT imaging. Patients were divided into three groups: (1) FESS with dental surgery without antrotomy, (2) FESS with intraoral antrotomy, and (3) intraoral surgery without FESS. The mean postoperative follow-up was 15 months. RESULTS: First group involved 64%, second group 31%, and third group 6% of the cases. The one-stage combined ENT and dental approach was used in 94% of cases (group 1 and 2) with a success rate of 97%. Concerning FESS, maxillary sinus surgery with middle meatal antrostomy only was performed in 54% of patients. Oroantral communication flap closure was performed in 56% of patients (success rate 98%). Healing was achieved within 3 months. The majority (87%) of patients were operated on unilaterally for unilateral findings. Over the past 18 years, a 6% increase of implant-related odontogenic sinusitis was observed. CONCLUSION: Odontogenic sinusitis is common, tending to be unilateral and chronic. Its dental source needs to be uncovered and treated and should not be underestimated. Close cooperation between ENT and dental specialists has a crucial role in achieving optimal outcomes. The one-stage combined surgical approach proves to be a reliable, safe, fast and effective treatment.
Keywords: dospělí; endoskopie; Maxillary Sinusitis; lidé; prospektivní studie; sinus maxillaris; Maxillary Sinus; Sinusitis; Prospective Studies; zánět čelistní dutiny; sinusitida; Adult; Endoscopy; Humans